THE EFFECT OF SPACE CHARGE ON PARTIAL DISCHARGES INCEPTION VOLTAGE IN AIR GAPS WITHIN HIGH DENSITY POLYETHYLENE - SEGHIER, T.; MAHI, D.; LEBEY2, T.; MALEC, D. (Courrier du Savoir; مجلد 10 (2010): Courrier du Savoir, 2010)
Partial discharges (PDs) which can occur in embedded voids in solid dielectrics depend on many factors, among them space charge which can seem to be one of the most relevant. As a matter of fact, under certain high voltage operating conditions, trapped or low-mobility electrically charged species within the insulation can give rise to space charge build up. These charges may have been the product of earlier PD events but they can also be the result of charge transport from the electrodes towards defect which can be contained within the insulation. This paper deals with the relation between space charge and partial discharges phenomena due to electrical stresses. Both simulation and experimental evidences of relations between partial discharge inception voltage (PDIV) and charge accumulation are investigated. PDs in trapped air-filled gaps between two adjacent insulated tapes made of high density polyethylene (HDPE) were measured. An amount of space charge is introduced on the cavity surface by negative direct current application (DC). An alternative current of increasing magnitude was then applied until PDs were initiated and observed. The voltages at which PDs initiate are measured for samples with and without space charge. It was shown that the larger the amount of space charge, the lower PDIV. Simulation results are in good agreement with those obtained from experiment.